The Response of Hotel Room Occupancy Rate in Fiji to Shocks: Empirical Evidence from Unit Root Tests with Endogenous Multiple Structural Breaks - Sami, Janesh (International Journal of Economics and Financial Issues, 2021)
Despite the political coup in December 2006 and Global Financial Crisis (GFC) in 2008, the tourism industry in Fiji has proven to be quite resilient. This article examines the response of hotel room occupancy rate in the tourism industry to domestic and external shocks using annual time series data from 1969 to 2019. We employ a suite of unit root tests accommodating for single and multiple endogenous structural breaks, and find that occupancy rate is a stationary process. The break dates coincide with the political coup in 1987 and Global Financial Crisis in 2007/2008. The results suggest that shocks are likely to have a temporary impact on the room occupancy rate in Fiji's tourism industry and the series will return to its trend path following an adverse shock. Keywords: Fiji, Hotel Room Occupancy Rate, Structural Breaks, Tourism, Unit Root JEL Classifications: C22, C29, Z30 DOI: https://doi.org/10.32479/ijefi.6948